HUBUNGAN PERSEPSI GURU TENTANG KUALITAS VISUAL MIND MAP DENGAN INTENSITAS PENGGUNAANNYA DI SEKOLAH DASAR - Eka Lestari, Meisya; Aisyah Az-Zahra, Aura; Salsabila, Awfa; Dita Cahyani, Rifka; Nurkhalifah, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT This study aims to examine the relationship between teachers' perceptions of the visual quality of mind maps and the intensity of their use in elementary school learning. The research employed a quantitative correlational approach using a survey method. The subjects consisted of 20 elementary school teachers from Makassar selected through total sampling. Data were collected using a structured questionnaire with a 4-point Likert scale comprising 20 items: Variable X (Teachers' Perception of Visual Quality of Mind Maps) with 10 items covering visual appeal, clarity of visual elements, readability and layout accuracy, and suitability with materials. Variable Y (Intensity of Mind Map Use) with 10 items covering frequency, diversity, consistency of use, and student involvement. Validity testing using Pearson Product Moment correlation (r-table = 0.444, n=20, α=0.05) showed 16 of 20 items were valid. Four negative-statement items (items 3, 6, 12, and 16) were declared invalid and excluded from further analysis. Reliability testing using Cronbach's Alpha yielded α = 0.70 for Variable X and α = 0.78 for Variable Y, both exceeding the minimum standard of 0.60. Descriptive statistics showed a mean score of 30.9 for Variable X and 28.3 for Variable Y from a maximum possible score of 40. Pearson correlation analysis yielded r = 0.632, exceeding r-table (0.444) and classified as a strong positive correlation. The coefficient of determination r² = 0.40 indicates that 39.97% of the variation in mind map use intensity is explained by teachers' perceptions of visual quality. These findings confirm a significant positive relationship between the two variables.